Serendipitous nostalgia tourism through literature – an autoethnographic story - Fusté-Forné, Francesc (2023)
This article discusses the relationships between nostalgia and tourism. While previous studies have analysed how film tourism stimulates nostalgic experiences, few studies have focused on the role of literature, and specifically children’s literature, in the creation of nostalgia destinations. Based on the symbiosis between Hans Cristian Andersen and Odense, in Denmark, this paper argues, from an auto ethnographic study, that literary tourism can also foster nostalgia tourism in a cultural destination.